A drive in SUVs: From development to disease. Issue 3 (4th March 2017) - Rao, Vinay Kumar; Pal, Ananya; Taneja, Reshma
ABSTRACT: Progression of cells through distinct phases of the cell cycle, and transition into out-of-cycling states, such as terminal differentiation and senescence, is accompanied by specific patterns of gene expression. These cell fate decisions are mediated not only by distinct transcription factors, but also chromatin modifiers that establish heritable epigenetic patterns. Lysine methyltransferases (KMTs) that mediate methylation marks on histone and non-histone proteins are now recognized as important regulators of gene expression in cycling and non-cycling cells. Among these, the SUV39 sub-family of KMTs, which includes SUV39H1, SUV39H2, G9a, GLP, SETDB1, and SETDB2, play a prominent role. In this review, we discuss their biochemical properties, sub-cellular localization and function in cell cycle, differentiation programs, and cellular senescence. We also discuss their aberrant expression in cancers, which exhibit de-regulation of cell cycle and differentiation.